Eco-Friendly Chitosan-Based Biodiesel Heterogeneous Catalyst Support Membrane - Retno Ariadi Lusiana; Rahmad Nuryanto; Nor Basid Adiwibawa Prasetya; Resa Putri Sherina; Dilla Dayanti (Jurnal Kimia Sains dan Aplikasi, 2023)
A chitosan-polyvinyl pyrrolidone K-30 (Cs-PVP.K30) membrane was prepared as a heterogeneous catalyst supporting membrane in the transesterification process in the production of biodiesel from palm oil and methanol through the blend reaction between chitosan (Cs) and polyvinyl pyrrolidone K-30 polymer (PVP K-30). Several membranes were characterized by their physicochemical and catalytic properties. Based on physicochemical data, it was found that including the carbonyl group from PVP K-30 into the chitosan framework correlated with an increase in porosity, hydrophilicity, water absorption, and the degree of swelling of the membrane. The results of the analysis using Fourier Transmittance Infra-red (FTIR) showed the spectra of carbonyl (-C=O) and hydroxyl (-OH) groups at wavenumbers 1648 cm-1 and 3363 cm-1, which shows that the reaction of chitosan alloy with PVP K-30 has been successfully carried out. The catalytic site of the Cs-PVP K30-NaOH membrane in the biodiesel production process was studied under several conversion conditions. It was found that the conversion of biodiesel reached 93.90% with a reaction time of 90 minutes, a temperature of 65°C, and an oil/methanol mole ratio of 1:7.